Effects of Dietary Seed Supplementation of Lagerstroemia speciose on Broiler Ability to Grow and Biochemical Traits Impacted by Commercial Feed Density - Sujatha, P. S.; Pavithran, S.; Ganesan, G.; Karthik, M.; Maivizhi, V. (Contemporary Research and Perspectives in Biological Science Vol. 2, 2024)
Aims: The present study aimed to investigate the effects of dietary seed supplementation on broiler ability to grow and biochemical traits that are impacted by commercial feed density and seed meal supplementation of Lagerstroemia speciosa. Background: Organic poultry production is becoming increasingly popular in India due to the ill effects of conventional farming, and consumers are willing to pay a premium for certified organic chicken meat. Materials and Methods: The research was carried out at the Government Arts College in Coimbatore-18, Tamil Nadu, India's Animal House, Department of Zoology, and Postgraduate and Research Department. The experimental design was divided into 5 groups. G1 normal diet served as a control, G2 fed green leafy vegetables and commercially available feed in G3, G4, and G5 served as coarse powder for experimental plant seeds, L. speciosa, and N. sativa (4.0 gm/100 gm). Results: The experimental animals show that the growth rate of the control group shows 41±3.21d initial weight and a 124±4bc final weight (6th week), while the growth rate of group II shows 135±4.04b. Body weight is a little higher than in the control group. Commercial feed is drastic in weight gain, and it shows 489±10.44a in group III. The experimental groups IV and V are active and healthier than the other groups, but the weight is poor in group IV 78±9.29d and 105±7.62bcd in group V. The N. sativa seeds consist of thymoquinone, a bio-compound to reduce the body weight 78±9.29d in Group IV. The control group has the highest concentration of urea (10.7±0.55a), while group IV has the lowest concentration. The amount of uric acid is lowest in group IV and largest in group V. Cholesterol levels are highest in group II (green leafy vegetables) and lowest in group IV. The supplementary diet, consisting of Tannins, flavonoids, Glycosides, and saponins, reduced feed intake by 50% compared to the control group. These compounds have appetite and digestion-stimulating properties and antimicrobial effects that aid digestion. Triglyceride levels are highest in Group V, while they are lowest in the control group. Group V has the least total protein, whereas the control group has the most. The control group has the highest albumin level, while group II has the lowest level. Conclusion: Lagerstroemia speciosa, especially, plays a crucial role in enhancing the growth and reproductive performance of broiler chickens, supporting organic farming, and helping farmers lower the cost of poultry feed.